Rapid Degradation of Host mRNAs by Stimulation of RNase E Activity by Srd of Bacteriophage T4 - Qi, Dan (Genetics, 2015)
Escherichia coli messenger RNAs (mRNAs) are rapidly degraded immediately after bacteriophage T4 infection, and the host RNase E contributes to this process. Here, we found that a previously uncharacterized factor of T4 phage, Srd (Similarity with rpoD), was involved in T4-induced host mRNA degradation. The rapid decay of ompA and lpp mRNAs was partially alleviated and a decay intermediate of lpp mRNA rapidly accumulated in cells infected with T4 phage lacking srd. Exogenous expression of Srd in uninfected cells significantly accelerated the decay of these mRNAs. In addition, lpp(T) RNA, with a sequence identical to the decay intermediate of lpp mRNA and a triphosphate at 5′-end, was also destabilized by Srd. The destabilization of these RNAs by Srd was not observed in RNase E-defective cells. The initial cleavage of a primary transcript by RNase E can be either direct or dependent on the 5′-end of transcript. In the latter case, host RppH is required to convert the triphosphate at 5′-end to a monophosphate. lpp(T) RNA, but not lpp and ompA mRNAs, required RppH for Srd-stimulated degradation, indicating that Srd stimulates both 5′-end-dependent and -independent cleavage activities of RNase E. Furthermore, pull-down and immunoprecipitation analyses strongly suggested that Srd physically associates with the N-terminal half of RNase E containing the catalytic moiety and the membrane target sequence. Finally, the growth of T4 phage was significantly decreased by the disruption of srd. These results strongly suggest that the stimulation of RNase E activity by T4 Srd is required for efficient phage growth.